Synthesis, physical-chemical and biological properties of 8-aminoderivatives of 7-(2-hydroxy-2-phenylethyl)theophylline - D. G. Ivanchenko (Zaporozhye State Medical University, 2016)
The search for new high-performance antimicrobial compounds remains one of the most important tasks of modern pharmaceutical chemistry, despite the wide range of modern natural, synthetic and semi-synthetic drugs for the treatment of infectious diseases. This is especially true for the naturally occurring compounds, new non-toxic and effective drugs can be created by their chemical modification for the treatment of various infectious pathologies. Recent researches in this area pay significant interest to new synthetic derivatives of xanthine. The aim of this paper is to elaborate simple laboratory methods of 8-aminoderivatives of 7-(2-hydroxy-2-phenylethyl)theophylline synthesis, unspecified in scientific papers earlier, and to study their physical, chemical and biological properties. Materials and methods of research. The melting point has been determined with the help of an open capillary method with PTP-M device. Elemental analysis has been performed with the help of the instrument Elementar Vario L cube, NMR-spectra have been taken on a spectrometer Bruker SF-400 (operating frequency of 400 MHz, solvent DMSO, internal standard - TMS). Study of antimicrobial and antifungal activity of synthesized compounds has been performed by two-fold serial dilution method. Standard test strains have been used for the study: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 885-653. Basic preparation solution has been prepared at a concentration of 1 mg in 1 mL of DMSO. Results and their discussion. Through the interaction of 8-bromotheophylline with the styrene oxide in propanol-1 environment was obtained an 8-bromo-7-(2-hydroxy-2-phenylethyl)theophylline, which under short-time heating up with primary amines of various structure or piperazine derivatives in aqueous dioxane or propanol-1 leads to the replacement of the bromine atom at the 8-position to form corresponding 8-aminosubstituted. Structure of synthesized compounds has been definitely proved by NMR-spectroscopy. Primary screening research of antimicrobial and antifungal activity of 8-aminosubstituted of 7-(2-hydroxy-2-phenylethyl)theophylline shows that these compounds reveal moderate and weak activity in concentrations 25-200 mcg/ml. Conclusions. Accessible laboratory methods have been elaborated for synthesis of 8-aminoderivatives of 7-(2-hydroxy-2-phenylethyl)theophylline. The NMR H1 spectral characteristics of the synthesized compounds have been analyzed and interpreted. Antimicrobial and antifungal activities of the obtained compounds have been explored. Priorities for further research of biologically active compounds have been outlined.